2011
DOI: 10.1002/jcp.22604
|View full text |Cite
|
Sign up to set email alerts
|

TGFBR3, a potential negative regulator of TGF‐β signaling, protects cardiac fibroblasts from hypoxia‐induced apoptosis

Abstract: A lot of evidence indicates that cardiac fibroblasts are essential for maintaining the structure and function of heart. The present study examined whether TGFBR3 (transforming growth factor type III receptor, also known as betaglycan) could prevent hypoxia-induced injury in neonatal mice cardiac fibroblasts, if so, its possible molecular targets. MTT, electron microscopy and TUNEL assay were used to identify cell viability and apoptosis in neonatal mice cardiac fibroblasts. Results showed that hypoxia for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 44 publications
(54 reference statements)
3
59
0
Order By: Relevance
“…Under H 2 O 2 conditions, an increase in TGFβR3 levels exerts a cumulative effect on the degree of apoptosis. Consistently, TGFβR3 is also known to enhance apoptosis in some tumor cells; however, TGFβR3 suppresses the apoptosis of cardiofibroblasts,7, 10 potentially by deactivating the TGFβR1/TGFβR2 complex to downregulate cell apoptosis 24. According to our data, TGFβR3 promotes cardiomyocyte apoptosis induced by myocardial infarction.…”
Section: Discussionsupporting
confidence: 84%
“…Under H 2 O 2 conditions, an increase in TGFβR3 levels exerts a cumulative effect on the degree of apoptosis. Consistently, TGFβR3 is also known to enhance apoptosis in some tumor cells; however, TGFβR3 suppresses the apoptosis of cardiofibroblasts,7, 10 potentially by deactivating the TGFβR1/TGFβR2 complex to downregulate cell apoptosis 24. According to our data, TGFβR3 promotes cardiomyocyte apoptosis induced by myocardial infarction.…”
Section: Discussionsupporting
confidence: 84%
“…As a member of this family, TGFBR3 acts as a coreceptor of TGF-b ligand, being a positive or negative regulator of TGF-b signals depending on the cellular context (42; 43). Recently, it has been shown that TGFBR3 may act as a protective factor in the apoptotic process of fibroblasts by negative regulation of TGF-b signaling (44). Our results further suggest that TGFB1 acts as a protective factor against docetaxel for DU-145 and PC-3 cells and has a partial role in the development of docetaxel resistance in cultured cells.…”
Section: Log Ratiosupporting
confidence: 78%
“…However, it is an extracellular protein, which does not lead to signal transduction. In fact, it may be a negative regulator of TGF-β function (Chu et al, 2011).…”
Section: Receptors and Signal Transduction Pathwaysmentioning
confidence: 99%